Aspectos físico-químicos e nutricionais da amêndoa e óleo de coco de babaçu (Orbignya phalerata Mart.) e avaliação sensorial de pães e biscoitos preparados com amêndoas - Costa, Ana Karoline de Oliveira (2014)
Babassu is the generic name given to oil palm belonging to the Palmae family and members of the genera and Orbignya Attalea. It is native of the transition zone between the cerrado and the Amazon rainforest. The potential use of babassu in several activities are large, since food and clothing until alternative energy elements. View of these facts, this study aimed to determine the chemical composition of almond, evaluate chemical, physical and physico-chemical aspects of babassu coconut oil removed by different methods of extraction and prepare bread and biscuit with ground almonds. The kernels of babassu coconut used in this study were from the city of Ipaporanga in the central hinterland of Ceará. By milling the bran (OpAM) was obtained laboratory oils. Babassu nut oil was removed by extraction with hot solvent (Soxhlet) (OpES) by hydraulic pressing (OpPH) and the solvent cold (Blight and Dyer) (OpEF). Two artisanal samples from the states of Pará (OpP) and Maranhão (OPM) were acquired. The chemical composition of the OpAM and its water activity were analysed. Samples OpPH, OpEF, OpM and OpP were analyzed for fatty acid composition, thiobarbituric acid reactive substances test, acid value, Rancimat induction period and color measurement. Cookie and bread with almond babaçu in its composition have been developed. The acceptance was evaluated by means of a structured hedonic scale of nine categories. OpAM has 2% protein, 49.5% fat, 42.4% carbohydrates and water activity of 0.67. No statistical differences were found between the techniques of extraction of babassu coconut that presents as major oil fatty acids saturated fatty acids, especially lauric (41,55%), myristic (14.58%) and the unsaturated oleic (15, 73%). No samples tested positive in the thiobarbituric acid reactive substances test. Also showed low levels of acidity. The babassu coconut oil showed good oxidative stability, high induction period. The samples tended to green and yellow colors, according to the parameters of the CIELAB scale. Cookie and biscuits prepared with ground almonds showed excellent sensory acceptance, taking the bread a slightly higher score.